Daur Ulang Sampah di Desa Paisbuloli Sulawesi Tenggara - Purnama Pasande; Ezra Tari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The problem of rubbish begins with the activity of disposal and burning in temporary landfills. The purpose of this service is to provide learning to the community on how to manage waste into plastic clothing; trash exchanged for rubbish, garbage exchanged for vegetables, recycled bags, eco-bricks for eggs, paving blocks, and paintings from used plastic bags. The methods used for waste management are: reducing, reusing, recycling, replanting, and replacing. Community service produces an important thing that is, it still encourages the community to be actively involved in managing waste. It is necessary to involve village officials to move the community to reduce waste. Moreover, there is training for the community to create jobs from waste recycling.